Body ideals for heterosexual romantic partners: Gender and sociocultural influences. (January 2015) - Murnen, Sarah K.; Poinsatte, Katherine; Huntsman, Karen; Goldfarb, Jesse; Glaser, Daniel
Highlights: Heterosexual college students made judgments about "ideal" bodies for romantic partners. Men placed more importance on body silhouettes they chose as ideal than women. The sexual permissiveness of men's peer groups predicted their ratings. Men's media use predicted their ratings. Women's agreement with adversarial sexual beliefs predicted their ratings. Abstract: In the present study, heterosexual college women ( N = 327) and men ( N = 160) were asked about their body type preferences for (hypothetical) romantic partners. Participants chose a particular silhouette value as ideal for a romantic partner, and rated how important it was to them for their partner to have this ideal body type. Men placed more importance on the body silhouette they chose for a partner than women did, and men's importance ratings were positively associated with the rated sexual permissiveness of their peer group and their total media use. Consuming sports media and watching reality television were the best media predictors of men's judgments about women's bodies. Less variability was explained in women's preferences for men partners' bodies, but endorsing adversarial sexual attitudes was positively related to judging the ideals chosen for men's bodies as important. Results were interpreted within both evolutionary and sociocultural theoretical frameworks.